Evaluation of resonant tunneling transmission coefficient from multilayer structures GaAlAs/GaAs - L. Moghaddasi (Iranian Journal of Physics Research, 2003)
A theoretical study of resonant tunneling in multilayered GaAlAs/GaAs structures are presented. The spectrum of resonant energies and its dependence on the barrier structure are analyzed from calculated profiles of barrier transparency versus energy, and from current voltage characteristics computed at selected temperatures and Fermi levels. The present formalism is based on the effective mass approximation and results are via direct numerical evaluations.